Localized Scleroderma Associated with Chronic Hepatitis C - Felipe Ladeira de Oliveira; Luisa Kelmer Côrtes de Barros Silveira; Maria Lourdes Candela Rambaldi; Fabio Cuiabano Barbosa (Case Reports in Dermatological Medicine)
Hepatitis C virus has been associated with various skin conditions, such as porphyria cutanea tarda and lichen planus, as an example. The objective of this paper is based on the description of a case of localized morphea, which came years after the discovery of hepatitis C, as well as a discussion of possible relations between both diseases.